2022
DOI: 10.1021/acsnano.2c09662
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Ribonucleoside Mono-, Di-, and Triphosphates Using an Engineered Nanopore

Abstract: Ribonucleotides, which widely exist in all living organisms and are essential to both physiological and pathological processes, can naturally appear as ribonucleoside mono-, di-, and triphosphates. Natural ribonucleotides can also dynamically switch between different phosphorylated forms, posing a great challenge for sensing. A specially engineered nanopore sensor is promising for full discrimination of all canonical ribonucleoside mono-, di-, and triphosphates. However, such a demonstration has never been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
1
19
0
2
Order By: Relevance
“…These measurements further confirmed that our observation of telegraphic switching from cis -diol binding to PBA is a consequence of dynamic interconversion between chiral boronate esters when observed in a single structure, and this conclusion is general when a large variety of analytes were tested. Though the same phenomenon may as well be carried out with a previously reported MspA nanoreactor however with the PBA placed at site 90, a significant reduction of the event amplitude was observed with halogenated catechols, suggesting that MspA-91PBA is optimum for the demonstration described in this paper (Figure S25). Though the observed two current levels are a result of interconversion between two chiral configurations, it is still a challenge to directly assign their absolute chiral states solely from the nanopore readout.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…These measurements further confirmed that our observation of telegraphic switching from cis -diol binding to PBA is a consequence of dynamic interconversion between chiral boronate esters when observed in a single structure, and this conclusion is general when a large variety of analytes were tested. Though the same phenomenon may as well be carried out with a previously reported MspA nanoreactor however with the PBA placed at site 90, a significant reduction of the event amplitude was observed with halogenated catechols, suggesting that MspA-91PBA is optimum for the demonstration described in this paper (Figure S25). Though the observed two current levels are a result of interconversion between two chiral configurations, it is still a challenge to directly assign their absolute chiral states solely from the nanopore readout.…”
Section: Resultssupporting
confidence: 76%
“…For simplicity, this modified MspA hetero-octamer is referred to in this paper as MspA-91PBA (Figure a). The modification site of MspA-91PBA differs from the previously reported MspA hetero-octamer, which is named MspA-90PBA. Since this MspA hetero-octamer has never been previously reported, a pore preparation protocol (Methods) along with plasmid design (Figure S1), pore purification by nickel affinity chromatography (Figure S2), and hetero-octamer purification by gel electrophoresis and gel extraction (Figure S3) are described here in detail.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A nucleotide sugar molecule, which simultaneously contains a nucleotide and a saccharide moiety, can in principle demonstrate two binding modes when monitored by MspA-90PBA. Binding to different moieties of the same molecule can also be regulated by the pH of the environment, a phenomenon that has also never been seen in any previous demonstrations using MspA-90PBA. ,, …”
mentioning
confidence: 68%
“…Binding to different moieties of the same molecule can also be regulated by the pH of the environment, a phenomenon that has also never been seen in any previous demonstrations using MspA-90PBA. [33][34][35]40,41 A variety of nucleotide and monosaccharide moieties and the linkage between them all contribute to the diversity of nucleotide sugars. Inspired by the success of UDP-Glc sensing, we expect that the same strategy may also be applied to the sensing of other nucleotide sugars.…”
Section: T H Imentioning
confidence: 99%